Implementation of bedside medication preparation in intensive care: post-improvement cycle - Ruy de Almeida Barcellos; Cindy Klagenberg Silva; Wiliam Wegner; Karina de Oliveira Azzolin; Luísa Brehm Santana; Mirella Zolner dos Santos (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To assess the implementation of the bedside medication preparation process in an Intensive Care Unit, following a quality improvement cycle. Method: A quasi-experimental study with non-paired samples, pre- and post-implementation, conducted in an Intensive Care Unit of a public hospital in southern Brazil, from September 2022 to April 2023, following the guidelines of the Standards for Quality Improvement Reporting Excellence 2.0. Adherence to bedside medication preparation, interruptions during preparation, adequate storage, identification and validity of multidose medications, and recording of storage refrigerator temperature were evaluated. Shapiro-Wilk and Mann-Whitney U tests were used for data analysis, and Carter's Positivity Index was used to determine compliance with observed practices. Results: Forty-five audits were conducted pre-intervention and 122 audits three months after the implementation of the improvement cycle. All variables showed significant improvements. Overall compliance increased from 46% to 80% in the pre- and post-implementation periods, respectively, indicating a transition from "undesirable" to "safe" care stratum. Conclusion: The study revealed a positive relationship between the implementation of a quality improvement cycle focused on medication preparation and improvements in patient safety.